KAJIAN USAHA OLAHAN SAGU (Metroxylion) DI KABUPATEN BANJAR PROVINSI KALIMANTAN SELATAN - Eddy Triatmoko; Subhan Fitriadi (Chlorophyl, 2019)
The Purpose of this research is to know revenue, the explicit cost and income sago processed